2022
DOI: 10.3390/ijerph19116630
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Activated Water for Food Safety and Quality: A Review of Recent Developments

Abstract: Plasma-activated water (PAW) has received a lot of attention lately because of its antibacterial efficacy and eco-friendly nature. Compared to traditional disinfectants, this novel and intriguing option has a high disinfectant capacity while causing little to no modifications to the foodstuffs. Until now, PAW has successfully demonstrated its effectiveness against a broad range of microorganisms on a wide variety of food items. Though the efficacy of PAW in microbial reduction has been extensively reviewed, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…Other authors who treated for example, chicken skin or muscle with PAW also found unchanged sensory characteristics [17] or deterioration [25]. According to Rahman et al [13], the reactive oxygen and nitrogen species (RONS) contained in PAW can influence the biochemical and sensory properties of a food either positively or negatively. With the current settings of our Tb-PAW, there is no evidence of a negative impact on the sensory properties of the products after spraying.…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors who treated for example, chicken skin or muscle with PAW also found unchanged sensory characteristics [17] or deterioration [25]. According to Rahman et al [13], the reactive oxygen and nitrogen species (RONS) contained in PAW can influence the biochemical and sensory properties of a food either positively or negatively. With the current settings of our Tb-PAW, there is no evidence of a negative impact on the sensory properties of the products after spraying.…”
Section: Groupmentioning
confidence: 99%
“…Many scientists have already tried various decontamination strategies to reduce the bacterial load of carcasses and achieve a simultaneous improvement in food shelf life, such Foods 2023, 12, 1113 2 of 15 as using chemicals (ethyl-Nα-lauroyl-L-arginate hypochloride, peracetic acid, or chlorinebased products), UV-C radiation, or different temperature regimes [9][10][11][12]. Unfortunately, these applications often cause negative effects on the products, such as damage to texture, alteration of taste, or formation of carcinogens [13]. Only the use of potable water to remove surface contamination on poultry meat is currently permitted due to European Regulation (EC) No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAW exhibits excellent antimicrobial activity against various bacteria, yeast, mold, and viruses (Thirumdas et al, 2018). Because of its antibacterial efficacy and eco-friendly nature, PAW has been successfully applied to improve the microbial safety and quality of various food products, such as fruits, vegetables, meat and fish products, edible mushrooms, fish, eggs, and cereal products (Liao et al, 2019;Rahman et al, 2022;Xiang et al, 2019b). It has been reported that the antibacterial efficacy of PAW is influenced by the plasma discharge type, working gas, plasma activation time, and treatment time (Shaw et al, 2018;Xiang et al, 2018;Xu et al, 2016).…”
Section: Influences Of Heating On the Antibacterial Efficacy Of Pawmentioning
confidence: 99%
“…Also, several biochemical reactions are triggered at the gas–liquid interface, and these reactive species are transferred to the liquids for producing broad-spectrum sanitizers. Literature suggests that PAL can inactivate many microorganisms and is exceptionally powerful in removing toxins from agricultural products without altering the taste, aroma, nutritional quality, physical attributes, and textural properties [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%